Leveraging Aircraft Avionics for Fleet and Airport Management. Issue 1 (2016) - McNamara, Margaret; Mott, John; Bullock, Darcy
Airport operations count data are used for a variety of purposes ranging from allocation of FAA Airport Improvement Program funding to environmental assessments and budget justification. Operations counts are difficult to obtain at small, nontowered airports, which constitute the majority of airports in the United States, and counts frequently are estimated unscientifically by airport managers. Current acoustic and video counting technology is limited, but with the FAA NextGen mandate for installation of automatic dependent surveillance–broadcast (ADS-B) out transponders by January 1, 2020, transponder data are emerging as a viable data source for other than traditional NextGen applications. The NextGen literature has focused on the use of this technology for navigation, safety, and airspace management. This paper introduces a method of applying ADS-B data to fleet management and airport operations. With a 1, 090-MHz receiver and appropriate signal processing hardware and software, Mode S and Mode S extended data can be used to track runway operations and fleet usage accurately and cost-effectively. This paper reviews the development of a low-cost portable hardware device and algorithm for obtaining both airport operations count and fleet utilization data. Approximately 1.1 million records collected from sites adjacent to the Purdue University Airport, Indianapolis (Indiana) International Airport, and Paris Charles de Gaulle International Airport are used to provide several examples of airport operations and fleet utilization reports.